Add the last two equations to eliminate <em>x</em> :
(<em>x</em> - 2<em>y</em> - 3<em>z</em>) + (- <em>x</em> + <em>y</em> + 2<em>z</em>) = 0 + 3
- <em>y</em> - <em>z</em> = 3
<em>y</em> + <em>z</em> = -3
Subtract this from the first equation to eliminate <em>z</em>, then solve for <em>y</em> :
(2<em>y</em> + <em>z</em>) - (<em>y</em> + <em>z</em>) = -8 - (-3)
<em>y</em> = -5
Plug this into the first equation to solve for <em>z</em> :
2(-5) + <em>z</em> = -8
<em>z</em> = 2
Plug both of these into either the second or third equations to solve for <em>x</em> :
<em>x</em> - 2(-5) - 3(2) = 0
<em>x</em> = -4
Answers:
angle2 = 160 degrees
angle3 = 10 degrees
============================================
Explanation:
The two triangles are congruent. We can prove this using SSS. The upper triangle is a mirrored copy of the lower triangle.
Since angle1 = 160 degrees, this means angle2 = 160 also. This is because the corresponding pieces of congruent triangles match up. Or you could use the second part of the hint which says "Opposite angles in a rhombus are congruent".
Let x be the measure of angle 3. For either isosceles triangle, it has congruent base angles measured x degrees. They add to the 160 degrees mentioned earlier to get a total of 180.
160+x+x = 180
2x+160 = 180
2x = 180-160
2x = 20
x = 20/2
x = 10
Angle 3 is 10 degrees.
Answer:
300x.03 all divided by 4
Step-by-step explanation:
Answer:
its 4
Step-by-step explanation:
Answer:
27.5
Step-by-step explanation:
pythagorean theorem. a^2+b^2=c^2.
so 12^2+b^2=30^2
meaning 144+b^2=900
900-144=756
square root 756
b=27.5